Variability on the energy properties of charcoal and charcoal briquettes for barbecue. Issue 8 (August 2022) - Mencarelli, A.; Cavalli, R.; Greco, R.
Abstract: In recent years there has been a strong increase in interest in the world of barbecues and outdoor cooking in high-income countries. Referring to FAO data, an exponential growth in imports of charcoal was observed in Europe and North America. Italy is one of the major European consumers and importers. On the market it is possible to find material with different characteristics and origins. However, analysis aimed at ascertaining the quality of the material are poorly performed. This research aimed to analyze the energy properties of charcoal commonly available on the Italian market. Twenty-four bags of charcoal and charcoal briquettes were analyzed. Eighteen samples represent the products most easily found on the market, in stores and on websites. In addition, six samples were supplied directly by the producer/importing company. The samples were grouped according to the continent of origin of the material (Europe, North-Central America and South America). Charcoal briquette samples were included together in a group. Referring to the ISO 17225-1 standard, the moisture content, ash content, heating value, volatile matter and fixed carbon were determined. Except for the moisture content, the results of the tests performed on all parameters show a strong variability both between different groups and within the same group. In detail, the European charcoal samples show characteristics more suitable for their use in barbecues. These have the highest values of fixed carbon and heating value and, at the same time, low values of ash and volatile matter. On the contrary, charcoal briquettes have less suitable characteristics for barbecue. The work also highlighted some gaps in the reference standard relating to laboratory analyses. To ensure careful control of the qualitative characteristics of the products on the market, it is necessary to promote the creation of a quality brand. Highlights: Absence of information on the characteristics of the charcoal on the market. Properties influenced by origin, wood species and production process. Presence of gaps in reference standards relating to laboratory analysis. High variability of the energy properties of the charcoal and briquettes. Poor representativeness of the HHV0 determined as indicated by the standard. Abstract : Charcoal; Charcoal briquettes; Charcoal properties; Proximate analysis; Barbecue; Heating value; Biofuel; Grilling.